Settlement Behavior of Soft Subgrade Reinforced by Geogrid-Encased Stone Column and Geocell-Embedded Sand Cushion: A Numerical Analysis - Jia-Jun Gao; Hui Xu; Jian-Wen Qian; Yi-Fan Gong; Liang-Tong Zhan; Ping Chen (Advances in Civil Engineering)
The geosynthetic-encased vertical column and geosynthetic-embedded horizontal cushion are recognized as the effective methods to reduce the settlement of the soft subgrade. This paper investigated the settlement behavior of a soft subgrade reinforced by geogrid-encased stone column and geocell-embedded sand cushion using the finite element analysis method (Plaxis 2D). The simulating settlement was in good agreement with the field monitoring data, indicating the reasonability of the designed model and adopted parameters. After that, the factors, geocell layer in sand cushion, encasement length around stone column, and standing time between embankment filling stages, were employed to study their influences on the subgrade settlement. The results showed that the embedment of geocell reduced construction settlement, postconstruction settlement, and differential settlement is attributed to the increase in stiffness of sand cushion and therefore the uniform distribution of additional stress on subgrade surface. When the encasement length of stone column increased from 1D (one time the column diameter) to 8D (full encasement), the settlement in construction stage and postconstruction stage decreased by 32.2% and 35.1%, respectively, which is benefited from the increase in the compression modulus of the column. The maximum lateral deformation occurred at the position of about 2D from the top of the stone column, and it decreased more significantly when the encasement length increased from 1D to 4D than that from 4D to 8D. The encasement length up to 4D is found to be adequate in reducing the subgrade settlement and the column lateral deformation based on the consideration of performance and economy. The extension of the filling interval increased the construction settlement caused by soil consolidation, while it decreased the postconstruction settlement.